2013
DOI: 10.1093/neuonc/not055
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-128 coordinately targets Polycomb Repressor Complexes in glioma stem cells

Abstract: MiR-128 is an important suppressor of PRC activity, and its absence is an early event in gliomagenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 70 publications
(60 reference statements)
6
91
0
1
Order By: Relevance
“…Western blot analysis was performed as described previously (13). Protein levels were quantified by Bradford assay (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was performed as described previously (13). Protein levels were quantified by Bradford assay (30).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, miR-128 inhibits tumor growth and angiogenesis by targeting p70S6K1 (10), promotes cell-cell adhesion in U87 glioma cells via regulation of EphB2 (11) and modulates glioma progression by regulating the SNAI1, miR-128 and SP1 axis (12). miR-128 has been demonstrated to target polycomb repressor complexes in glioma stem cells, mediating cancer stem cell maintenance and radioresistance (13). miR-128 has also been demonstrated to serve a role in other types of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, miR-128-3p overexpression did not significantly suppress the expression levels of these four genes in T-ALL cell lines (Online Supplementary Figure S4). In addition, we tested other validated miR-128-3p target tumor suppressor genes in other tumor entities including BAX 13 and E2F5 14 (and SUZ12 15 and NF1…”
Section: Evaluation Of Possible Regulation Of Other Validated and Prementioning
confidence: 99%
“…We have shown that miR-128 coordinately targets both PRC components PRC1 by targeting B lymphoma Mo-MLV insertion region 1 homolog (BMI1) and PRC2 by targeting suppressor of Zeste 12 Homolog (SUZ12), epigenetic regulators of chromatin status. MiR-128 mediated inhibition of both PRCs blocks their partially redundant function [52] and associated chromatin modifications. Stable overexpression of miR-128 in GSCs changed their molecular landscape by downregulating signaling pathways related to the maintenance of stemness properties.…”
Section: Microrna and Glioblastoma Stem Cellsmentioning
confidence: 99%